Application of Image Media in Improving Children's Speaking Skills in PAUD - Kontisa, Emilia; Palupi, Aisyah Putri Dea (International Journal Education and Computer Studies (IJECS), 2024)
Early Childhood Education (ECE) plays a crucial role in laying the foundation for children's development, particularly in language skills. Speaking skills are essential for fostering critical thinking and communication abilities from an early age. This study aims to explore the application of image media in storytelling methods as a tool to enhance children's speaking skills at PAUD Aisyah, Pajar Tinggi Village, Pajar Bulan District, Lahat Regency. The study employed a Classroom Action Research (CAR) approach, conducted in two cycles, each consisting of three meetings. The results demonstrated a significant improvement in children's speaking skills following the implementation of image media. The children were able to articulate sentences more effectively and showed an increase in vocabulary usage. Image media proved to be effective in creating an engaging learning environment, motivating children to actively participate in learning activities. This study confirms that using image media in language learning at ECE can have a positive impact on the development of children's speaking skills.